Sea freight forwarding business- in depth study of Kuehne + Nagel Bangladesh Ltd - Shihab, Azmal Bashir (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.